2004
DOI: 10.1002/eat.20033
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity as a risk factor for eating disorder behavior: Assessment implications with adolescents

Abstract: These results provide moderate support for the idea that impulsivity serves as a risk factor for the onset of eating disorder behavior. However, this is only true when more objective behavioral measures were utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 33 publications
7
74
0
1
Order By: Relevance
“…Martin et al, 2000;Wonderlich et al, 2004) and that children"s early eating behaviours have been shown to be relatively stable (Ashcroft, Semmler, Carnell, van Jaarsveld & Wardle, 2008), identifying associations between eating behaviours and temperamental traits at an early age could potentially be useful for clinicians and healthcare professionals working with children with feeding problems and with those who are, or are at risk of, overweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin et al, 2000;Wonderlich et al, 2004) and that children"s early eating behaviours have been shown to be relatively stable (Ashcroft, Semmler, Carnell, van Jaarsveld & Wardle, 2008), identifying associations between eating behaviours and temperamental traits at an early age could potentially be useful for clinicians and healthcare professionals working with children with feeding problems and with those who are, or are at risk of, overweight.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, childhood temperament (specifically higher levels of negative emotionality) has been related to the development of later eating concerns (Martin et al, 2000). Finally, in adults, temperamental traits such as impulsivity have been linked with disordered eating attitudes and behaviours (e.g., Wonderlich, Connolly, & Stice, 2004). Thus, there is evidence to suggest that an individual"s temperament may be associated with later eating-related problems.…”
Section: Relationships Between Temperament and Eating Behaviours In Ymentioning
confidence: 99%
“…Even in non-clinical samples, impulsivity correlates with some aspects of eating behaviours, in particular eating disinhibition [103] , and seems to be a risk factor for ED behaviours [104] . A recent study on a large non-selected adolescent population sample found an association between bulimic behaviours and discontrol behaviours (bullying, truancy, excessive drinking, sexual dishinibition) [105] .…”
Section: Impulsivitymentioning
confidence: 99%
“…[7][8][9] Impulsivity has been shown to predict onset of BN symptoms 9 months later among adolescent girls in a community sample. 10 Individuals with BN, like youth with ADHD-C, 11 display inhibitory control deficits on a neuropsychological stop-signal reaction time task. 12 Despite this theoretical rationale, overall, in the ADHD literature, little is known about children's prospective risk for female-relevant psychopathology such as BN in adolescence, 13 and the BN literature needs more studies testing a developmental framework that incorporates childhood precursors of this disorder.…”
Section: Introductionmentioning
confidence: 99%